Deteksi Kebuntingan Dini Pada Kambing Peranakan Etawah (Capra aegagrus hircus) Berdasarkan Metode Non-Return Rate dan Reaksi Cubboni - Qori Solihah; Sumaryadi, Mas Yedi; Nugroho, Aras Prasetiyo (ANGON: Journal of Animal Science and Technology, 2020)
Background. Aims to determine and analyze the pregnancy rate of Etawah Crossbreed goats based on Non-return Rate method and Cubboni Reaction. Materials and methods. The materials used in this study were 20 Etawah Crossbreed goats, prostaglandins, urine, and concentrated H2SO4. The variables studied were the pregnancy rate of Etawah Crossbreed Goat based on Non-return Rate method and Cubboni Reaction. This study used an experimental method and the data obtained were processed using Chi Square analysis. Results. The analysis shows the number of x2<x2 tables (P>0.05), this means that the pregnancy detection method does not significantly affect the pregnancy rate of Etawah Crossbreed goats. Conclusion. Pregnancy rate of Etawah Crossbreed Goat based on Non-return Rate method amount 80% while based on Cubboni Reaction method amount 90%.